Depression and coping strategies among haemodialysis patients of Bagmati Province, Nepal - Yogi, Ishu; Ghimire, Raju; Subedi, Suraksha (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Haemodialysis is therapeutic procedure of purifying blood used for management of acute and chronic renal failure. Financial burden, dialysis and other treatment procedures also add as stressor among patients undergoing haemodialysis treatment. Depression is most frequent psychological problem reported by chronic kidney patients but is also underdiagnosed and underrated among them. The prevalence of depression is reported higher among chronic kidney patients undergoing dialysis treatment compared to general population with higher risk of deaths and hospitalization. This study aimed to assess the depression and coping strategies among haemodialysis patients of Bagmati Province. Methods: Quantitative cross-sectional study design was used in this research to collect the data from 3 Haemodialysis Centre viz. Kathmandu, Chitwan and Manthali as it covered the haemodialysis patients from Bagmati province. 370 participants were selected from Bagmati province of Nepal via simple random sampling technique. Nepali language version of Hospital Anxiety and Depression Scale (HADS) and Brief COPE Inventory scale were used to measure the depression and coping mechanism among the respondents. The descriptive and inferential statistics was used for data analysis. Results: Nearly two-fifths (38.6%) of the respondents showed the symptoms of depression followed by no depression (35.9%) and borderline depression (25.4%). There was significant association between level of depression and coping strategies. Conclusions: The finding from the study highlight the high prevalence of depressive symptoms. There is significant association between level of depression and coping strategies indicating need for targeted mental health intervention including promotion of effective coping mechanism in the targeted population.